2021
DOI: 10.1155/2021/9208634
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA-29b and Sclerostin Levels Correlate with Coronary Artery Calcification and Cardiovascular Events in Maintenance Hemodialysis Patients

Abstract: Objective. Coronary artery calcification (CAC) is a common complication in end-stage renal disease (ESRD) patients undergoing maintenance hemodialysis (MHD), and the extent of CAC is a predominant predictor of cardiovascular outcomes in MHD patients. In this study, we sought to uncover the relationship between circulating miRNA-29b, sclerostin levels, CAC, and cardiovascular events (CVEs) in MHD patients. Methods. This study recruited patients receiving MHD for at least three months in the Hainan General Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…Yang et al [ 78 ] reported that the under-regulation of miR-29 in serum samples may be considered an important signal of early identification of CAC. In agreement with this study, He et al [ 52 ] concluded that lower plasma levels of miRNA-29b may be used as independent risk factors for the incidence of cardiovascular events (CVEs) and CAC. Lu et al [ 54 ] focused their study on the role of miR-27b: high levels of this miRNA may predict the occurrence of asymptomatic carotid artery stenosis (ACAS), with a high risk of generating subsequent cerebral ischemia events (CIEs).…”
Section: Resultssupporting
confidence: 86%
“…Yang et al [ 78 ] reported that the under-regulation of miR-29 in serum samples may be considered an important signal of early identification of CAC. In agreement with this study, He et al [ 52 ] concluded that lower plasma levels of miRNA-29b may be used as independent risk factors for the incidence of cardiovascular events (CVEs) and CAC. Lu et al [ 54 ] focused their study on the role of miR-27b: high levels of this miRNA may predict the occurrence of asymptomatic carotid artery stenosis (ACAS), with a high risk of generating subsequent cerebral ischemia events (CIEs).…”
Section: Resultssupporting
confidence: 86%
“…Calcification of atherosclerotic plaques is secondary to the development of coronary artery disease. Early detection of coronary calcification is an important marker for early diagnosis [19][20][21][22][23][24]. MicroRNA is a factor related to the formation of atherosclerosis that has been concerned in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miRNAs have surfaced as novel regulators of biological processes across nearly all organ systems, and a growing body of research is establishing connections between disrupted miRNA function and various disease mechanisms. However, the utility of miRNAs as therapeutic biomarkers for assessing the impact of physical exercise on HD patients is still debated [14][15][16][17][18]. Therefore, this review discusses the modulation of circulating miRNAs in CKD patients on dialysis treatment who engage in physical exercise.…”
Section: Introductionmentioning
confidence: 99%